2012
DOI: 10.1128/aem.01794-12
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Mutagenesis of Planctomyces limnophilus and Analysis of a pckA Mutant

Abstract: A Planctomyces limnophilus mutant generated using the EZ-Tn5 transposome was found to possess an insertion within pckA, encoding phosphoenolpyruvate carboxykinase. Disruption of pckA expression and elimination of enzymatic activity resulted in poor growth in glucose-free medium, demonstrating a gluconeogenic role for pckA in P. limnophilus. Bacteria belonging to the phylum Planctomycetes possess several distinctive phenotypic and molecular characteristics, including a proteinaceous cell wall that is devoid of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…2A). This marks the first instance a directed gene knockout has been made in the phylum Planctomycetes; all other studies have employed random transposon insertion (33,47). We confirmed that the selectable marker replaced pvmJ by PCR genotyping (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…2A). This marks the first instance a directed gene knockout has been made in the phylum Planctomycetes; all other studies have employed random transposon insertion (33,47). We confirmed that the selectable marker replaced pvmJ by PCR genotyping (Fig.…”
Section: Resultssupporting
confidence: 67%
“…We focused on the gene complement in P. limnophilus as the representative BMC-associated gene cluster because this species is rapidly becoming a model organism with which to study planctomycete biology (33,47). We compared its composition to that of the EUT and vitamin B 12 -dependent PDU BMC loci found in S. enterica and to the glycyl radical enzyme utilizing the PDU (hereafter referred to as PDU2) BMC locus found in C. phytofermentans (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It catalyzes the guanosine or adenosine mononucleotide-dependent reversible conversion of oxaloacetate and PEP. In many bacteria, the inactivation of this enzyme significantly affects the growth or survival of cells when organic acids (e.g., acetate, lactate, succinate, and malate) are used as the sole carbon and energy sources (71)(72)(73)(74). In the present study, we observed that the PEPCK gene (pck; NONO_c74450) is also essential for SH22a to grow on GP and rubber.…”
Section: Resultssupporting
confidence: 51%
“…as an exception to [ 11 ] or as a variation of [ 12 ] the classical Gram-negative cell plan. P. limnophilus has been established as model organism for the phylum, as it is the first and only species of Planctomycetes that has been genetically modified [ 13 , 14 ]. Here we present a summary classification and a set of features for P. brasiliensis IFAM 1448 T , together with the description of the complete genomic sequencing and annotation, as well as a re-assessment of the taxonomy of the group based on phylogenomic as well as traditionally sampled characters.…”
Section: Introductionmentioning
confidence: 99%